Luteolin-7-O-Glucoside Present in Lettuce Extracts Inhibits Hepatitis B Surface Antigen Production and Viral Replication by Human Hepatoma Cells in Vitro - Cui, Xiao-Xian; Yang, Xiao; Wang, Hui-Jing; Rong, Xing-Yu; Jing, Sha; Xie, You-Hua; Huang, Dan-Feng; Zhao, Chao (Frontiers in Microbiology, 2017)
Hepatitis B virus (HBV) infection is endemic in Asia and chronic hepatitis B (CHB) is a major public health issue worldwide. Current treatment strategies for CHB are not satisfactory as they induce a low rate of hepatitis B surface antigen (HBsAg) loss. Extracts were prepared from lettuce hydroponically cultivated in solutions containing glycine or nitrate as nitrogen sources. The lettuce extracts exerted potent anti-HBV effects in HepG2 cell lines in vitro, including significant HBsAg inhibition，HBV replication and transcription inhibition, without exerting cytotoxic effects. When used in combination interferon-alpha 2b (IFNα-2b) or lamivudine (3TC), the lettuce extracts synergistically inhibited HBsAg expression and HBV replication. By using differential metabolomics analysis, Luteolin-7-O-glucoside was identified and confirmed as a functional component of the lettuce extracts and exhibited similar anti-HBV activity as the lettuce extracts in vitro. The inhibition rate on HBsAg was up to 77.4%. Moreover, both the lettuce extracts and luteolin-7-O-glucoside functioned as organic antioxidants and, significantly attenuated HBV-induced intracellular reactive oxygen species (ROS) accumulation. Luteolin-7-O-glucoside also normalized ROS-induced mitochondrial membrane potential damage, which suggests luteolin-7-O-glucoside inhibits HBsAg and HBV replication via a mechanism involving the mitochondria. Our findings suggest luteolin-7-O-glucoside may have potential value for clinical application in CHB and may enhance HBsAg and HBV clearance when used as a combination therapy.